Relationships Between Clinically Measured Upper-Extremity Physical Characteristics and Ball Spin Rate in Professional Baseball Pitchers. Issue 5 (May 2021) - Wong, Regan; Laudner, Kevin; Evans, Daniel; Miller, Luke; Blank, Trent; Meister, Keith
Abstract : Abstract: Wong, R, Laudner, K, Evans, D, Miller, L, Blank, T, and Meister, K. Relationships between clinically measured upper-extremity physical characteristics and ball spin rate in professional baseball pitchers. J Strength Cond Res 35(5): 1331–1337, 2021—During baseball pitching, physical characteristics of the shoulder, elbow, wrist, hand, and fingers have been hypothesized to be critical to creating ball spin. The purpose of this study was to determine if pitchers with greater shoulder, elbow, wrist, and finger range of motion (ROM), arm and hand length, wrist strength, or grip and finger strength would produce greater ball spin than those with less physical characteristics. Ninety, asymptomatic, professional baseball pitchers participated (age = 24.5 ± 3.9 years; height = 189.9 ± 6.1 cm; body mass = 92.6 ± 10.6 kg). Goniometers and a digital level were used to measure shoulder, elbow, wrist, and finger ROM, a tape measure was used to assess arm and hand lengths, and handheld dynamometers were used to measure wrist, grip, and finger strength. Ball spin was measured using a 3-dimensional Doppler radar and video system. Standard multiple regression analyses showed no significant relationships existed between ball spin and any of the upper-extremity ROM or limb length variables ( R 2 = 0.01–0.03; p = 0.40–0.94). However, there was a significant relationship for the summation of wrist strength ( R 2 = 0.24, p = 0.03). Both time to wrist extension strength B = 0.50 (95% confidence interval [CI]: 0.23–0.76), p = 0.001 and radial deviation strength ( B = 0.41 [95% CI: 0.15–0.66], p = 0.002) were significant predictors within this model. These results demonstrate that the rate of ball spin during a pitch may be partially altered by increasing wrist extension acceleration and radial deviation strength. However, the subsequent clinical measurements of shoulder, elbow, wrist, and finger ROM, arm and hand length, and grip and finger strength were not associated with ball spin.